Peran Kepala Sekolah sebagai Edupreneur dalam Transformasi Sekolah yang Unggul - Arif, Sofiyudin (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2024)
The main problem in the world of education is the lack of development of Edupreneurial leadership, involving uncertainty of roles, resource constraints, conflict management, teacher performance assessment, and relationships with parents and the community. Therefore, this research aims to investigate effective strategies that can be used by school principals as Edupreneurs in creating excellent school transformations, with a focus on identifying Edupreneurship principles into school policies and practices. This research uses a literature review research method with a descriptive analysis type. From the research, it is found that the role of the school principal as an edupreneur in directing school transformation through a combination of transformational, distributive, and servant leadership models, supported by innovation diffusion strategies, organizational learning, strategic management, and change management, forms a solid framework for achieving educational excellence.